Toward Better Care for Sickle Cell Disease in Nigeria: A Review of Challenges and Interventions - Grace, Valentine Olagunju; Ayobami, Tosin Adegbenro; Suleiman, Zakari; Victoria, Ayomide Olagunju (Journal of Diseases, 2025)
With more than 150,000 affected infants annually, Nigeria bears the largest burden worldwide of sickle cell disease (SCD), making it a significant public health concern. The management of SCD in Nigeria is challenging, despite advancements in medical research and increased knowledge. This review examines the numerous issues surrounding SCD in the nation, including the financial burden on affected families, the lack of specialized care facilities, the absence of newborn screening programs, the sociocultural stigmatization of SCD, and restricted access to high-quality healthcare. Additionally, inadequate public health education and a lack of coordinated national policies result in delayed diagnosis and suboptimal treatment outcomes. We also highlighted recent efforts and recommendations aimed at improving early detection, comprehensive care, and community support. Addressing these challenges through expanded health education and enhanced healthcare infrastructure is essential to reducing morbidity and mortality associated with SCD in Nigeria.
Keywords: Sickle Cell; Nigeria; Early Diagnosis; Public Health